THE ROLE OF MICROELEMENTS IN THE HUMAN BODY (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Metal ions are required to maintain human health, as several essential biological functions in humans depend on their presence, and their absence or deficiency can lead to diseases. However, some metal ions, particularly heavy metals such as mercury and lead, can be hazardous due to their toxic effects.